The concept of Javanese cultural locality that influences the design of the Aerotropolis Hotel Yogyakarta International Airport - Kenneth Nathalio Alexander; Hartanto Budiyuwono; Baskoro Tedjo (Jurnal Indonesia Sosial Teknologi, 2024)
The government has plans to build an Aerotropolis area, a city with an airport-centered infrastructure and economic topology with the aim of supporting local economic progress at Yogyakarta International Airport, Kulon Progo. The potential for rapid airport traffic means that the planned hotel development can be a facility for postponing plane departure schedules due to certain circumstances such as bad weather (incidental). Hotel development is implemented using a Javanese cultural locality approach which revives the atmosphere of traditional elements by creating local building shapes and patterns. So the issues raised are the concept of locality and the concept of hotel design. This research uses qualitative descriptive methods and analysis is carried out using theories from the architectural anatomy approach and the Javanese cultural locality approach. The result is that there are five aspects of architectural anatomy and three cultural forms that influence the locality of Javanese culture. The anatomical aspects of architecture are the environmental scope, site scope, building scope, form scope, and material scope, while the aspects of cultural form are the form of ideas, activities, and artifacts. Five architectural concept criteria were produced, namely the concept of an imaginary mountain-sea axis, Kiblat Papat Kalima Pancer, Javanese architectural buildings, Kawung batik ornaments, and local materials aimed at giving the impression of a building that is integrated with the area and still preserves Javanese culture.